Writing development in K-Pop stan Twitter communities - Dinda Alifia Darmawan; Lidiyatul Izzah (Concept : Community Concern for English Pedagogy and Teaching, 2022)
This research focuses on the use of language in social interactions, specifically within the context of K-Pop fans using social media platform Twitter to communicate with other fanbases. The study aims to determine the impact of the K-Pop community on Twitter on the writing skills of high school students in English. The research method employed is quantitative, using a sample of 100 high school students who are members of the K-Pop community on Twitter for at least a year and have studied English. Data was collected using a Likert scale. Results of the analysis indicate a significant effect of the Twitter community on the development of student's writing skills in English Keywords: Twitter; K-Pop; Writing